Prophylactic effect of retromuscular mesh placement during loop ileostomy closure on incisional hernia incidence: a multicentre randomised patient- and observer-blind trial (P.E.L.I.O.N trial) - Müller, Sven; Weyhe, Dirk Alfons; Herrle, Florian; Horvath, Philipp; Bachmann, Robert; von Ehrlich-Treuenstätt, Viktor; Heger, Patrick; Nasir, Nadir; Klose, Christina; Ritz, Alexander; Sander, Anja; Grohmann, Erich; et al. (Trials, 2023)
Incisional hernia is a frequent complication following loop ileostomy reversal. Incisional hernias are associated with morbidity, loss of health-related quality of life and costs and warrant the investigation of prophylactic measures. Prophylactic mesh implantation at the time of surgical stoma reversal has shown to be a promising and safe method to prevent incisional hernias in this setting. However, the efficacy of this method has not yet been investigated in a large multicentre randomised-controlled trial (RCT) with adequate external validity. The P.E.L.I.O.N. trial will evaluate the efficacy of prophylactic mesh reinforcement after loop ileostomy closure in decreasing the rate of incisional hernia versus standard closure alone.
Gesehen am 22.03.2023